A new strategy to alleviate the obesity induced by endocrine disruptors—A unique lysine metabolic pathway of nanoselenium Siraitia grosvenorii to repair gut microbiota and resist obesity. (May 2023) - Wang, Yu; Sun, Wei; Yan, Sen; Meng, Zhiyuan; Jia, Ming; Tian, Sinuo; Huang, Shiran; Sun, Xiaoxuan; Han, Shihang; Pan, Canping; Diao, Jinling; Wang, Qiuxia; et al.
Abstract: Obesity caused by endocrine disruptors (EDCs) has become a hot topic threatening human health. Recently, Nanoselenium Siraitia grosvenorii (NSG) has been shown to have potential health-modulating uses. Based on the results of 16S rRNA sequencing and metabolomics analysis, NSG has the unique function of improving gut microbiota and inhibiting obesity. Specifically, NSG can enhance gut microbiota diversity and change their composition. A significant positive correlation exists between the liver change in lysine and the high-importance dominant species ([ Ruminococcus]_gnavus, Alistipes_finegoldii, etc.). NSG metabolites analysis showed that the lysine level increased by 44.45% and showed a significantly negatively correlated with (TG, TC, Leptin, etc.). Significantly, NSG reduces the degradation of lysine metabolism in the liver and inhibits fatty acid β-oxidation. In addition, NSG decreased Acetyl-CoA levels by 24% and regulated the downregulation of TCA genes ( CS, Ogdh, Fh1, and Mdh2 ) and the upregulation of ketone body production genes ( BDH1 ). NSG may have a positive effect on obesity by reducing the participation of Acetyl-CoA in the TCA cycle pathway and enhancing the ketogenic conversion of Acetyl-CoA. In conclusion, the results of this study may provide a new dietary intervention strategy for preventing endocrine disruptor-induced obesity. Graphical abstract: Image 1 Highlights: Nanoselenium Siraitia grosvenorii reshapes gut microbiota disrupted by imidacloprid. Liver lysine metabolism is linked to obesity caused by endocrine disruptors. Apigenin may regulate the contribution of acetyl coenzyme A to energy metabolism. Nanoselenium Siraitia grosvenorii is a potential candidate for improving obesity.